دور الحِبْس في تعليم القرآن - شاويشد. عبدالمجيد محمود محمد (Aljameai, 2022)
الملخص: تهدف هذه الدراسة إلى إبراز الدور المهم الذي لعبه الحبس ولا يزال في الحفاظ على تعليم القرآن الكريم، وأيضاً ترغيب الناس في حبس الأموال لعظيم أجرها عند الله. وأما عن المنهج المتبع لتحقيق أهداف هذه الدراسة، فإن الباحث - بإذن الله- سيستخدم المنهجين الاستقرائي لجمع المعلومات من مظانها والوصفي لوصف واقع الحبس في زمننا هذا. فقد جاءت الدراسة مشتملة على مقدمة وثلاثة مباحث وخاتمة بها أهم النتائج والتوصيات التي توصل إليها الباحث. Abstract: This study aims to highlight the important role that imprisonment has played and is still playing in preserving the teaching of the Noble Qur’an, as well as enticing people to withhold money for its great reward with God. As for the method used to achieve the objectives of this study, the researcher - God willing - will use the two inductive methods to collect information from its perspective and descriptive to describe the reality of imprisonment in our time. The study included an introduction, three chapters, and a conclusion with the most important findings and recommendations reached by the researcher.